Vegetation and land-use data collection methods for environmental management purposes, with particular reference to the rivers entering False Bay, Cape, South Africa - O'Callaghan, M (Department of Biological Sciences, 2016)
The increasing population and urbanization occurring in South Africa is threatening the survival of many environments, particularly those in close proximity to urban areas. Present legislation does not adequately protect the environment, and methods are needed to collect data to guide the development of conservation-orientated management and developmental policies. These data should provide a general description of the environment, Indicating sensitive areas, while taking physical, socio-economic and natural features into account. To be most meaningful, these data should be stored in a survey information system which is accessible to any person or institution involved in management or developmental policy formulation. Chapter 2 describes some of the components of such a system. Chapter 3 discusses the data collection component of the survey Information system. The use of vegetation features to describe the natural environment, and the use of land-use features for the socio-economic environment, are emphasized. Numerous methods are available to collect vegetation and land-use data, but for management purposes the methods should be elementary enough to be used by non-specialists while still supplying meaningful data. Aerial photography can be applied to vegetation and land-use studies. However, numerous inaccuracies can occur when using aerial photography as a source of data and Chapter 3 also discusses some of these limitations. The study area used to test proposed methods of collecting vegetation and land-use data for a management information system are described in Chapter 4. The study area consists of eleven study sites, each at a river mouth on the False Bay coast.